2022
DOI: 10.3389/fpls.2022.1055779
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of NCED leads to the accumulation of carotenoids in the flesh of F1 generation of peach hybrid

Abstract: Flesh color is an important target trait in peach [Prunus persica (L.) Batsch] breeding. In this study, two white-fleshed peach cultivars were crossed [Changsong Whitepeach (WP-1) × ‘Xiacui’], and their hybrid F1 generation showed color segregation of white flesh (BF1) and yellow flesh (HF1). Metabolome analysis revealed that the flesh color segregation in the hybrid F1 generation was related to the carotenoid content. The decrease in β-carotene and β-cryptoxanthin in BF1 flesh and increase in β-cryptoxanthin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The flesh were ground to a fine powder for experiments in liquid nitrogen. The content of carotenoids in the flesh was determined by the acetone-extraction method according to Song et al. (2022a) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flesh were ground to a fine powder for experiments in liquid nitrogen. The content of carotenoids in the flesh was determined by the acetone-extraction method according to Song et al. (2022a) .…”
Section: Methodsmentioning
confidence: 99%
“…Pathway maps illustrating the key metabolites and genes related to fructose metabolism were generated using TBtools ( Chen et al., 2020 ) and Adobe Illustrator 2021. Total RNA extraction and quantitative real-time polymerase chain reaction (qRT-PCR) analysis were conducted according to the protocol outlined by Song et al. (2022a) .…”
Section: Methodsmentioning
confidence: 99%
“…Different peach varieties produce red mesocarp if accumulating anthocyanins and yellow mesocarp if accumulating carotenoids, while white peaches do not accumulate high levels of either pigment ( Cantín et al , 2009 ). Consumers prefer yellow peaches in Western countries but white varieties in Eastern countries ( Song et al , 2022 ). As discovered by analysing 35 genotypes, ancestral species of peach display white flesh, and during domestication, a mutation in a carotenoid cleavage dioxygenase resulted in yellow-flesh peaches with different flesh color.…”
Section: Stone Bearing Fruitsmentioning
confidence: 99%
“…As discovered by analysing 35 genotypes, ancestral species of peach display white flesh, and during domestication, a mutation in a carotenoid cleavage dioxygenase resulted in yellow-flesh peaches with different flesh color. Furthermore, an F 1 population of a white × yellow cross revealed that down-regulation of the 9-cis-epoxycarotenoid dioxygenase gene also produced yellow traits ( Song et al , 2022 ). White and yellow peaches do not differ only in flesh color, but also display a different aroma repertoire.…”
Section: Stone Bearing Fruitsmentioning
confidence: 99%
“…Furthermore, NCED genes have been observed to evolve relatively slowly (Song et al, 2022). This slow rate of evolution might play a role in the functional divergence of NCED subfamilies across different tissues.…”
Section: Introductionmentioning
confidence: 99%